Living with the Genie : essays on technology and the quest for human mastery - Lightman Alan (Island Press, 2003)
A group of remarkably penetrating, frank, and expert scientists, techno-wizards, activists, and writers raise provocative questions about what is gained and what is lost in a world enthralled by technology in this wonderfully soulful forum on life in the 'Wired World.' " -BOOKLIST